External Validation of the KOOS-ACL in the MOON Group Cohort of Young Athletes Followed for 10 Postoperative Years. Issue 6 (May 2023) - Marmura, Hana; Tremblay, Paul F.; Bryant, Dianne M.; Spindler, Kurt P.; Huston, Laura J.; Getgood, Alan M.J.
Background: The Knee injury and Osteoarthritis Outcome Score–Anterior Cruciate Ligament (KOOS-ACL) is a short form version of the KOOS, developed to target populations of young active patients with ACL tears. The KOOS-ACL consists of 2 subscales: Function (8 items) and Sport (4 items). The KOOS-ACL was developed and validated using data from the Stability 1 study from baseline to postoperative 2 years. Purpose: To validate the KOOS-ACL in an external sample of patients matching the outcome's target population. Study Design: Cohort study (diagnosis); Level of evidence, 1. Methods: The Multicenter Orthopaedic Outcomes Network group cohort of 839 patients aged 14 to 22 years who tore their ACLs while playing sports was used to assess internal consistency reliability, structural validity, convergent validity, responsiveness to change, and floor/ceiling effects of the KOOS-ACL at 4 time points: baseline and postoperative 2, 6, and 10 years. Detection of treatment effects between graft type (hamstring tendon vs bone–patellar tendon–bone) were also compared between the full-length KOOS and KOOS-ACL. Results: The KOOS-ACL demonstrated acceptable internal consistency reliability (α = .82-.89), structural validity (Tucker-Lewis index and comparative fit index = 0.98-0.99; standardized root mean square residual and root mean square error of approximation = 0.04-0.07), convergent validity (Spearman correlation with International Knee Documentation Committee subjective knee form = 0.66-0.85; Western Ontario and McMaster Universities Osteoarthritis Index function = 0.84-0.95), and responsiveness to change across time (large effect sizes from baseline to postoperative 2 years; d = 0.94 [Function] and d = 1.54 [Sport]). Stable scores and significant ceiling effects were seen from 2 to 10 years. No significant differences in KOOS or KOOS-ACL scores were detected between patients with different graft types. Conclusion: The KOOS-ACL shows improved structural validity when compared with the full-length KOOS and adequate psychometric properties in a large external sample of high school and college athletes. This strengthens the argument to use the KOOS-ACL to assess young active patients with ACL tears in clinical research and practice.